Ternary MoWSe2 alloy saturable absorber for passively Q-switched Yb-, Er- and Tm-doped fiber laser - Ahmad, Harith; Reduan, Siti Aisyah; Aidit, Siti Nabila; Yusoff, Norazriena M.; Maah, Mohd Jamil; Ismail, Mohammad Faizal; Tiu, Zian Cheak (Elsevier, 2019)
A ternary molybdenum tungsten selenide (MoWSe2) alloy is proposed and demonstrated as a saturable absorber (SA) to induce Q-switching in the 1. 0μm, 1. 5μm and 2.0μm regions. The MoWSe2 based SA is fabricated by mechanical exfoliation and sandwiched between two fiber ferrules to complete the fiberized SA assembly. The MoWSe2-SA is integrated into ytterbium, erbium and thulium-doped fiber laser cavities, and stable self-starting Q-switched pulses are observed at 1038 nm, 1554 nm and 1964 nm respectively. Maximum repetition rates at 120.2 kHz, 48 kHz and 61.5 kHz are observed at these wavelengths, along with corresponding pulse widths as narrow as 0.96 μs, 1.9 μs and 2.4 μs respectively. These results validate the performance of MoWSe2 as a broadband SA for Q-switching operation, offering new opportunities of ternary transition metal dichalcogenide alloys in future photonics devices.